Systemic therapy of cutaneous melanoma - Krzakowski, Maciej (Contemporary Oncology/Współczesna Onkologia, 2003)
Current UICC/AJCC classification for the staging of cutaneous melanoma reflects the progress in the knowledge on the biology of this neoplasm. The prognosis of cutaneous melanoma may be well established based on pathological and clinical parameters. The natural course of melanoma is highly aggressive, which is expressed by the potential for even small primary lesions to metastasize. Surgical treatment is an essential therapeutic modality in patients with melanoma. The role of systemic therapy is still a matter of clinical trials. Today’s systemic therapy modalities include the use of biological agents (e.g. interferon a and interleukin 2), and cytotoxic agents (e.g. dacarbazine, vinblastine, cisplatin, carmustine, temozolomide). As regards the systemic therapy for melanoma, most controversies surround the use of high-dose interferon a as adjuvant therapy for high-risk patients, and the use of biological agents in combination with chemotherapy as first-line treatment for the metastatic disease. Both issues should be still tested within clinical trials. Further studies should evaluate the duration of adjuvant therapy with interferon a, best-tolerated schedule of interferon a administration, the role of adjuvant interferon a and interleukin 2 in intermediate-risk patients, and the value of biochemotherapy in adjuvant and palliative settings. This review represents an attempt to discuss current evidence on the place of adjuvant and palliative systemic therapy in melanoma.